Unmet Family Planning Needs among Women in the Child Bearing Period in Benin: Prevalence and Possible Associated Risk Factors - Amboise Tchando Nahini; Emmanuel N’Kou´e Sambieni; Mouftaou Amadou Sanni (New Ideas Concerning Arts and Social Studies Vol. 1, 2025)
Developing countries, including Benin, are characterized by very high fertility. The consequences result in the precarious health of women and children, slow economic growth, poverty, overcrowding of schools and health facilities, overload of infrastructure and depletion of natural resources. Additionally, high fertility rates contribute to rising unemployment, increasing social inequalities, and the escalation of social conflicts. This article assesses the unmet needs for family planning among women of childbearing age in the Donga department, Benin. This goal is therefore to guide the intervention strategies of the various projects and programs aimed at filling the unmet needs in family planning for the achievement of the Sustainable Development Goals (SDGs), and the well-being of the Beninese population in general and that of Donga in particular. A mixed method (quantitative and qualitative) was used based on data from a field survey conducted among 466 women of childbearing age in 280 households and 57 resource people. The qualitative component carried out through observations, in-depth individual interviews with resource people, and focus group discussions with homogeneous subgroups of women, men, and young people, provided explanations and information to complete the quantitative component. In addition, the collection of quantitative data was carried out electronically from smartphones using a digital questionnaire using CS PRO version 6.3 software. To this end, multiple correspondence analysis (MCA) and logistic regression were used to identify the profiles of women with unmet needs and the factors associated with them. The results indicate that 89.6% of unmet needs concern birth spacing, while 10.4% concern birth control. The explanatory multivariate analysis made it possible to identify the woman’s age, the ideal number of children, the type of household the woman belongs to, the woman’s area of residence, her level of education, and her main occupation as significant determinants of unmet need for birth spacing. As for unmet needs for birth control, only the woman’s age group and ideal number of children had a significant influence at the 5% threshold. In-depth interviews with resource persons highlighted that education is a central element influencing the unmet need for family planning. Adult women face considerably higher unmet needs compared to teenagers, while cultural norms around ideal family size significantly reduce unmet needs for those preferring larger families. Other factors such as place of residence, education level, employment status, and type of union show trends that warrant further investigation but do not have statistically significant impacts in this study. The study recommended improving awareness about family planning services by promoting education for all, integrating sexual and reproductive health into school curricula, and raising awareness not only among women but also among men.